Forrmation of Si - Ge Alloy Nanocrystals: First-Principles Calculation - Nguyen, Truong Giang; Le, Thanh Cong; Nguyen, Duc Dung; Ngo, Ngoc Ha; Tran, Van Quang (Old Journal, 2018)
In this report, we employed first-principles calculation within the framework of density functional theory in generalized gradient approximation to analyze the stability of Si1-xGex alloys (x=0.0625, 0.1875; 0.3125; 0.6250 and 0.8125) in face-centered cubic (FCC) crystal-structure. The results show that the substitution of Ge atoms into Si sites is stable with the relevant compositions and the lattice constant of the alloy is gradually increased with the composition x. These are in good agreement with experimental results obtained from analyses of Si-Ge nanocrystals prepared by co-sputtering method.